SELF-EDUCATION AND WAYS OF TEACHER COMPETENCE FORMATION - Ruhangiz Aliyeva (Scientific Journal of Polonia University, 2023)
The main aim of the article is to explore the self-education and ways of teacher competence formation. In the context of rapid informational flow, a number of high requirements are imposed on school education in the era of scientific and technological progress.The school should not only equip the younger generation with scientific knowledge, but also instill in them the skills of independent acquisition of knowledge, free labor skills, intellectual work culture, independent thinking, self-education, better readiness for independent work. This is one of the important directions of modern education reform. Self-education is one of the very necessary rings in a united complex intellectual work. This type of activity, which includes elements of independent activity, was in the center of attention in all structures and stages of public life as a means of improving socio-political and vocational training and acquiring knowledge by a person, besides has always attracted people with progressive views and has been highly appreciated it basing on its" utility coefficient”. Very little attention was paid to the work on the organization and implementation of self-educational activities of specialists engaged in professional activities, it was not considered as a means corresponding to self-educational upbringing, personal development and self-control skills.It should be added that in pedagogy there is no complete concept on self-education and teacher competence.